Determinant of Intention E-cigarettes Use Among a Sample of Senior High School Students in Surabaya - Hendra Eka Alifiyanto; Sri Widati; Rachmat Hargono (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The prevalence of smoking in Indonesia in 2018 among adolescents (10-18 years old)was 9.1%. Surabaya has 9,28% of boys who are active smokers and acknowledged smoking everyday. Adolescents using conventional cigarettes are also tend to be interested to using e-cigarette.Objective: The aim of this study was to analyze the factors that associate the intention of e-cigarettes use inadolescents in Surabaya.Method: The type of study was observational analytic design with cross sectional. The sample size wasdetermined by cluster random sampling, in 8 school which includes 291 students. Data collection wasthrough filling out the online questionnaire and analyzed using logistic regression test to determine theassociation between variables.Results: This results of this study show that the factors that have positively associated to intentions ofe-cigarettes use by adolescent are instrumental attitudes (3,035), injunctive norm (2,561), descriptive norm(4,896) and self efficacy (3,526). Experiential attitude and perceived control did not associated the intentionof adolescents e-cigarette use.Conclusion: Providing education to adolescents, parents and educational stakeholders about the dangers ofusing e-cigarettes and restrictions on adolescents access to e-cigarettes should take considered the long-termimpact of e-cigarette.